(untitled) (Journal of Partial Differential Equations, 1996)
The aim of this paper is to discuss the extinction and positivity for the non-Newtonian polytropic filtration equation ∂u∂t = ∂∂x(|∂u^m∂x|^p-2∂u^m∂x) with m > 0, p > 1.